JURIDICAL ANALYSIS OF EMPLOYEE CONSIDERATIONS AS ADMINISTRATIVE COMPETITION AGENCY - Marbun, Robinsar (Veteran Law Review, 2020)
The Personnel consideration Agencyhas the authority to carry out the administrative appeals process from the reception of the file until it considers, making the decision whether strengthened or scaled or cancelled as per the weight the violation is done in question. The decree is certainly signed by the Chairman and Secretary of BAPEK. This research aims to analyze the administrative appeals to the personnel consideration body as a final step in the administration appeals process, and then see the whole problem solving if there is a arbitrariness Stand out in the allotment of disciplinary penalties as in articles 3 and 4, namely the obligations and prohibitions to be complied with. The source of this research is used with two sources of legal resources, namely the primary legal source, which is the study of interviews to speakers who are competent in implementing the problem of resolving administrative appeals dispute and secondary legal source, namely data Obtained from the literature study by reading, quoting, and studying legislation, documents, books, dictionaries, and other literature relating to the issues to be discussed.